Determinants of Customer Satisfaction and Intention to Reuse Mobile Food Ordering Apps Among Vietnamese Consumers - Hoang Anh, Vu Thi (International Journal of Global Economics and Management, 2024)
The article utilizes a quantitative method to study the factors influencing consumer satisfaction and intention to continue using food delivery applications on mobile devices in Vietnam. The research team applies a research model based on the extended Unified Theory of Acceptance and Use of Technology (UTAUT2) and adds four factors to suit the Vietnamese market: Online Reviews, Online Positioning, Perceived Risk, and Innovativeness. The research results show that satisfaction and the intention to continue ordering food via mobile applications are influenced by key factors such as social influence, hedonic motivation, price, online reviews, and online positioning. These findings suggest several important managerial implications for online food service providers.